A prospective and observational study on complications of type 2 diabetes mellitus in correlation with body mass index - Siddarama, R.; Thrinath, G.; Bhagyasree, J.; Anjum, S. Afshaan; Anjanamma, R. (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study is to observe the prevalence of complications of diabetes mellitus (Type 2) among patients and to minimize their occurrence through patient education. The study helps to assess the clinical data of patients with diabetes mellitus (Type 2) along with the analysis of patterns, frequencies and predictive factors of microvascular, macrovascular complications and to educate and minimize the complications of diabetes mellitus among patients. Methods: Prospective and observational study was conducted among the type 2 diabetes mellitus patients at Sree Diabetes Clinic for a period of 6 months. The patients were interviewed using the patient data collection form which included demographic details, chief complaints and different diagnostic tools to detect type of complications. Both micro and macrovascular complications were evaluated. Results: A total of 150 type 2 diabetic cases were collected. Out of these 38(25.33%) patients were having BMI <25, and 112(74.67%) were having BMI ≥25 (overweight and obese). Out of 150 diabetic cases collected, a total of 131 diabetic complications were found. Out of these, 64(42.6%) were neuropathy, 3(2%) were nephropathy, 20(13.3%) were retinopathy and 17(11.3%) were having cardiovascular complications. Out of 112 patients with BMI ≥25, 60(54%) were found to have diabetic complications and out of 38 patients with BMI <25, 18(47%) were found to have diabetic complications. 90 out of 150 patients had a history of hypertension and 17 out of 150 patients had an abnormal lipid level. Conclusions: In this study, author found that obesity is a major risk factor for the development of diabetes mellitus and its complications.